Zigbee 기반 AoA 위치인식 시스템 실험 및 구현 - 조호성; 박철영; 박대헌; 박장우; Cho, Ho-Seong; Park, Chul-Young; Park, Dae-Heon; Park, Jang-Woo (한국항행학회논문지, 2011)
The technique of localization is the core technology for information exchange or environment monitering to measure the position of an object or person. Today, the techniques of localization have been studied extensively and it can be applied to logistics, medical, robotics, etc. But, a lot of money to apply technique of localization is needed. Hence in this paper, we proposed AoA localization system based on Zigbee at low cost. The System measured the RSSI value by rotating the directional antenna using a step motor and Zigbee module. When the measured RSSI is the largest, the receiver measures the angles from beacons which are located at the corners with the rotating angle of a stepping motor and the position of the receiver will be calculated by appling AoA localization method. The measured results show an error about 35~36 cm. 위치인식 기술은 사물이나 사람의 위치를 측정하여 서로 정보를 교환하고 환경을 제어하는데 필요한 핵심기술이다. 현재도 위치인식 기술은 다양한 방법들로 연구되고 있으며, 물류, 의학, 로봇 분야 등에 적용될 수 있다. 그러나 위치인식 기술을 적용하려면 많은 비용이 필요하다. 이에 본 논문에서는 적은 비용으로 구현 가능한 Zigbee기반 AoA 위치인식 시스템을 제안한다. 본 시스템은 흔히 이용하는 스텝 모터, 지향성 안테나, Zigbee 모듈을 사용하여 비컨에 지향성 안테나를 회전시켜 RSSI값을 측정하였다. RSSI값이 가장 큰 값을 가질 때 스텝 모터의 회전각을 계산하여 수신기가 위치한 각도를 판단하고 AoA 방식을 적용하여 수신기의 위치를 측정하였다. 수신기의 위치를 옮겨가며 측정한 결과 35~36cm 정도의 오차가 있었다.